ANALISIS TAPAK BUKIT KATUNUN - Rinakanti Rinakanti; Ahmad Jauhari; Siti Erdian (Jurnal Hutan Tropis, 2021)
The purpose of this site analysis is to determine business space and public space in accordance with Regulation of the Director General of Sustainable Production Forest Management Number P.06 / PDASHL / SET / KUM.1 / 11/2016 concerning Guidelines for Designing a Site Design for Management of Natural Tourism in Protected Forests. The analysis method of identifying satellite imagery in 2018 with the use of Quantum software can create slope class maps and land cover maps. These results are then checked randomly in the field. This site analysis was prepared by referring to the provisions of the Minister of Environment and Forestry Regulation Number P.22 / Menhut-II / 2012 concerning Guidelines for Business Activities Utilizing Natural Tourism Environmental Services in Protected Forests, Regulation of the Director General of Sustainable Production Forest Management Number P.06 / PDASHL /SET/KUM.1/11/2016 concerning Guidelines for Designing a Site for Management of Nature Tourism in Protected Forests. Site Analysis is a dynamic reference for planners to divide Bukit Katunun natural tourism area into business space and public space. Business space will be built restaurant / café, lodging, paid camping ground, swimming pool and agrotourism area. While public spaces will be built gates (2 pieces) and security posts, information and health centers, parking areas, gathering areas + toilets, parks + fountains, free camping ground, halls / meeting rooms, research centers, viewing towers and shelters ( 4 pieces), and a trail (jungle tracking) ± 2000 m.